THE ROLE OF VERTICAL INTEGRATION IN MANAGING TRANSFORMATION PROCESSES - TRETIAK, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article explores the role of vertical integration in managing transformation processes in agricultural enterprises. Vertical integration is a strategic tool that enables businesses to effectively adapt to changes in the market environment and enhance their competitiveness. The study shows that vertical integration contributes to improved coordination of production units and optimizes the resource potential of enterprises, which in turn reduces costs and increases economic efficiency. Moreover, integration allows agricultural enterprises to control all stages of the production process — from raw material cultivation to its processing and distribution — ensuring greater resilience to external risks and reducing dependence on intermediaries.The article also examines the risks and challenges associated with vertical integration. These include the increasing complexity of managing many processes and the concentration of resources, making the enterprise more vulnerable to market fluctuations and legislative changes. Examples such as PJSC "MHP," PJSC "Kernel," and PJSC "Astarta," which implement vertical integration strategies in their operations, are cited. These companies face challenges in managing large volumes of internal operations as part of their integrated structures.The article concludes that vertical integration is a crucial factor in transforming the production structures of agricultural enterprises, enhancing their efficiency and resilience in today's market. However, a flexible approach to process management and the development of appropriate adaptation mechanisms to external challenges are necessary to implement integration strategies successfully. Additionally, companies implementing vertical integration must invest in modern technologies to improve production efficiency and reduce operational costs. Vertical integration also helps businesses maintain product quality by controlling the production chain and strengthening their market position. Enterprises that successfully integrate vertically are better positioned to handle supply chain disruptions and increase their ability to respond to market demand fluctuations. Furthermore, vertical integration allows firms to scale operations, offering a competitive edge in both local and international markets. Lastly, this strategy promotes long-term sustainability by allowing companies to mitigate the risks associated with external suppliers and market volatility.
Keywords: vertical integration; transformation processes; management; agricultural enterprises; production structures; integrated enterprises; economic efficiency